Role of Artificial Intelligence in Cost Reduction and Competitiveness Achievement - Sadeq Dhahir Farhan Alzaidi; Hussein Falah Hasan (Green Economics: International Journal of Islamic and Economic Education, 2025)
The research addresses the role of artificial intelligence technologies in achieving cost reduction, achieving a sustainable competitive advantage, and improving the operational performance of companies, by analyzing how these technologies reduce costs. The research is based on a basic hypothesis that "artificial intelligence technologies contribute positively to reducing costs for economic units by improving the efficiency of using available resources, reducing waste, and improving technical innovations, which enhances the ability of the economic unit to compete and achieve a sustainable competitive advantage." The research recommends investing in artificial intelligence technologies, training employees to use them effectively, developing a clear strategy, adopting analytical models to measure the impact of artificial intelligence on performance and costs on a regular basis, and supporting research related to developing artificial intelligence applications to improve operational efficiency and enhance cooperation between universities and economic units to develop innovative solutions that achieve a sustainable competitive advantage. This research is an addition to the literature concerned with how economic units adopt artificial intelligence technologies and work to reduce their operating costs, and aims to provide a practical framework for economic units seeking to improve their financial performance by adopting the latest artificial intelligence technologies.